Distributed, ambient and pervasive interactions : technologies and contexts : 6th International Conference, DAPI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: technologies and contexts : 6th International Conference, DAPI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part II (2018) - Unknown
No abstract available